Socio-economic characteristics and attitudes of organic and non-organic consumers in Lima, Peru - Higuchi, Angie; Avadi, Ángel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
Profiling organic and conventional consumers through their socio-economic characteristics while determining the main reasons that drive purchase of organic products are necessary to increase organic food consumption in Modern Metropolitan Lima. This study’s purpose was to 1) illustrate the demographic characteristics of organic and conventional consumers and 2) depict an assessment of the attitudes of the conventional consumers who are willing to purchase organic food in the future. The survey, carried out between April and November 2014 at organic shops in Lima, involved interviews with 145 consumers who consume conventional products and 164 consumers who consume organic products. The analysis includes a discriminant analysis, which was used to determine whether consumers purchase conventional or organic, as well as also cross tables that depicted an assessment of the attitudes of the conventional consumers regarding their willingness to purchase organic food in the future. The results suggested that educational attainment has a positive effect on the likelihood to be a conventional consumer. Additionally, health attributes and access to organic foods seem to predict conventional consumers’ future organic purchasing behavior.